Dimerized Translationally Controlled Tumor Protein-Binding Peptide 2 Attenuates Systemic Anaphylactic Reactions Through Direct Suppression of Mast Cell Degranulation - Cho, Hyunsoo; Park, Jiyoung; Kim, Hyo Kyeong; Hwang, Eun Sook; Lee, Kyunglim (Frontiers in Pharmacology, 2021)
Dimerized translationally controlled tumor protein (dTCTP) amplifies allergic responses through activation of several types of immune cells and release of inflammatory mediators. In particular, dTCTP plays an important role in histamine release by triggering mast cells and has been proposed as a target in the treatment of allergic diseases. dTCTP-binding peptide 2 (dTBP2) is known to attenuate severe allergic rhinitis and asthma through inhibition of dTCTP activity on airway epithelial cells and T cells; however, it is unclear whether dTBP2 affects mast cell function and mast cell disease. In this study, we explored the effects of dTBP2 on mast cell degranulation and allergen-induced anaphylactic reactions. We found that bacterial product lipopolysaccharide increased the expression of dTCTP in mast cells and rapidly released dTCTP by the mast cell stimulator compound 48/80. Interestingly, the released dTCTP further promoted mast cell degranulation in an autocrine activation manner and increased calcium mobilization in mast cells, which is essential for degranulation. Furthermore, dTBP2 directly and dose-dependently inhibited in vitro mast cell degranulation enhanced by compound 48/80, suggesting a direct and potent anti-anaphylactic activity of dTBP2. dTBP2 also significantly suppressed the dTCTP-induced degranulation and histamine release through inhibition of the p38 MAPK signaling pathway and suppression of lysosomal expansion and calcium mobilization in mast cells. More importantly, in vivo administration of dTBP2 decreased mortality and significantly attenuated histamine release and inflammatory cytokine production in compound 48/80-induced systemic anaphylactic reactions. These results suggest that dTBP2 is beneficial for the control of anaphylaxis with increased dTCTP.